A tactile sensor using a conductive graphene-sponge composite. Issue 17 (14th April 2016) - Chun, Sungwoo; Hong, Ahyoung; Choi, Yeonhoi; Ha, Chunho; Park, Wanjun
Abstract : A simple method for highly sensitive and flexible graphene-sponge composites and their application toward tactile sensing is reported. Abstract : For sensors that emulate human tactile perception, we suggest a simple method for fabricating a highly sensitive force sensor using a conductive polyurethane sponge where graphene flakes are self-assembled into the porous structure of the sponge. The complete sensor device shows a sensitive and reliable detection response for a broad range of pressure and dynamic pressure that correspond to human tactile perception. Sensitivity of the sensor to detect vibration is also confirmed with vertical actuations due to slipping over micro-scale ridge structures attached on the sensors. Based on the sensor's ability to detect both pressure and vibration, the sensor can be utilized as a flexible tactile sensor.